Learners’ Abilities in Solving Math Story Problems: A Lesson Learned from Young Language Learners - Fitriyani; Mustika, Dea (Journal of Language and Literature Studies, 2024)
The importance of young language learners’ understanding in solving math story problems in the 21st century learning era is crucial, because this ability is not only the key to competition in the world of work but also essential in developing students' critical logic, creativity, and independence in solving everyday problems. This study aims to measure students' ability to solve math story problems by using qualitative and descriptive quantitative methods. The data from this study is presented in the form of paragraphs describing the test results, with 20 fourth-grade elementary school students as respondents who worked on 10 essay questions. Data collection techniques were carried out through test results, interviews, and documentation. Furthermore, data analysis data display, reducing, and drawing conclusions. The results showed that young language learners’ ability to solve story problems can be seen from several indicators. The average value for the ability to write known aspects is 21.50, for the ability to write aspects that are asked is 12.67, for the ability to solve math problems is 55, and for the ability to write conclusions is 59. With an overall student average score of 37.04, it can be concluded that the ability of students in the class can be categorized as less.